The Correlation Between Emotional Intelligence and English Achievement Among High School Students - Nurcahyana, Waode; Susanti, Susanti (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2025)
This study investigates the correlation between Emotional Intelligence (EI) and English achievement among second-grade senior high school students. Utilizing an ex post facto design, data were collected from 116 students via questionnaire and document study. Emotional intelligence was measured using an adaptation of Goleman’s model. Results indicated that students’ EI levels were predominantly in the “high” and “very high” categories. However, the correlation between EI and English achievement was very low (r = .137, p = .142). Despite the weak overall correlation, the motivation component of EI demonstrated a significant contribution to students’ English performance. The findings suggest that while EI may not strongly predict language achievement, specific EI components, particularly motivation, play a crucial role in supporting language learning.‎ Keywords:‎ emotional intelligence, English achievement, high school students, motivation, language learning